Radiological Determination of the Femoral Neck Axis Length and its Male-Female Variations in Adult Bengali Bangladeshis - Riad, Md Riadul Zannat; Akter, Khalada; Amin, Nahid Farhana (Eastern Medical College Journal, 2024)
Background: A neck femur fracture is one of the common fractures in osteoporotic people. It produces physical and economic burdens due to its adverse consequences. There is a correlation between the femoral neck length and a fractured neck femur. It is existence that have a significant sex-specific differences in the geometrical parameters of the proximal femur. Proximal femur exhibits important sexual dimorphism and has considerable potential for forensic purposes. The objective of the present study is to measure and compare the radiological femoral neck axis length between males and females in adult Bengali Bangladeshi Population. Materials and Methods: This cross-sectional analytical study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from March 2019 to February 2020with ethical clearance from respective IERB. For this study, A total of 200 femoral necks were analyzed from 100 patients’ radiographs comprising 50 males and 50 females. Results: The average Femoral neck axis length (FNAL) is 10.65±0.57 cm and 9.59±0.47 cm in adult Bengali Bangladeshi males and females respectively.The mean femoral neck axis length (FNAL) is 10.09±0.74 cm for the right femur and 10.15±0.76 cm for the left femur. Conclusion: The femoral neck axis length in adult Bengali Bangladeshi males was significantly higher than the females. There are no significant differences of femoral neck axis length between the right and left femur. Eastern Med Coll J. July 2024; 9 (2): 95-99